First-principles study of solid methane at high pressure - Pantha, Nurapati; Acharya, Jagaran; Adhikari, Narayan Prasad (BIBECHANA, 2014)
We study the structural and electronic properties of solid methane of space group P212121 at high pressure. The density-functional theory (DFT) based first-principles calculations within the Generalized Gradient Approximations (GGA) have been performed by using Quantum Espresso package. Our findings show that the solid methane in orthorhombic structure compresses fast at the first, and then slowly as a function of elevated hydrostatic pressure. The pressure-volume diagram agrees with the available previously reported data up to pressure of around 200 GPa. In orthorhombic structure, solid methane is a wide band gap insulator at low pressures (tens of GPa). The band gap decreases with increase in the pressure. At high pressure (around 900 GPa), the band gap decreases to semi-conductor range (1.78 eV). Our results reveal that methane to be metallic above the pressure coverage of the present study which is consistent to the interior of the giant planets. The band gap as a function of pressure (from the present work) agrees well with the previously reported data. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11779BIBECHANA 12 (2015) 70-79